2017
DOI: 10.3389/fpsyg.2017.01279
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Cognitive Style and Job Level: First Demonstration of Cultural Differences

Abstract: Higher-level managers are said to have a more intuitive cognitive style. To verify this hypothesis, we must consider three factors that have often been left out of account. Previous studies, related to managerial cognitive style and job level, used a unidimensional model of cognitive style, did not consider age, and have mainly been conducted in the UK. Our study replicated previous studies on a population of 1,533 Japanese fulltime workers, using a questionnaire based on a two-dimensional model of cognitive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Thus, it is possible that managers who face high time pressures denote innovative behaviors even when they have a low NFC (Wu et al, 2014). In short, and beyond the already mentioned aspects, the NFC influences several areas in the sphere of the management, such as career guidance, personnel selection, task design, team composition, conflict management, and training and development (Allinson & Hayes, 1996; Hayes & Allinson, 1994; Kageyama & Sugiura, 2017).…”
Section: Need For Cognitionmentioning
confidence: 99%
“…Thus, it is possible that managers who face high time pressures denote innovative behaviors even when they have a low NFC (Wu et al, 2014). In short, and beyond the already mentioned aspects, the NFC influences several areas in the sphere of the management, such as career guidance, personnel selection, task design, team composition, conflict management, and training and development (Allinson & Hayes, 1996; Hayes & Allinson, 1994; Kageyama & Sugiura, 2017).…”
Section: Need For Cognitionmentioning
confidence: 99%
“…They used Pask's Holist-Serialist dimension of CS and found that not only did students show an improvement in learning when their styles were matched, but they showed more positive perception towards such learning systems. Kageyama and Sugiura (2017) conducted a first-of-its-kind cross cultural study of cognitive styles among higher level employees in UK and Japan. As opposed to the prevailing notion favouring intuitive style among higher level jobs, their study found quite the opposite in Japanese culture; where rational styles were more prevalent as levels went higher.…”
Section: Cognitive Styles In Applied Researchmentioning
confidence: 99%